Dynamic study of milling low depth channels - Rosca, Dorin Mircea; Vasiloni, Mircea Anton; Folea, Milena (MATEC Web of Conferences, 2017)
This paper presents a study of dynamic aspects of the milling cutters used in particular case of low depth channels. A new calculation method was developed, taking into account the high variations of cutting forces during milling small depth channels with peripheral cutting tools. A new formula was established for the minimal value of channel depth that allows cutting process to be performed in conditions of dynamic stability.